The amazing Spider-Man. Vol. 11, Last remains - Spencer, Nick (Marvel Worldwide, Inc., 2021)
"Spider-Man just took the beating of his life... but we're just getting started. Prepare yourself for the horrors of Last Remains! Kindred - the mystery villain who has been plaguing Peter Parker's life from the shadows - is stepping out on stage for the first time...and Spider-Man is not ready for the havoc that will result. Now, the wallcrawler must seek out the aid of one of his oldest allies - Doctor Strange, the Sorcerer Supreme. But it's not going to be enough. In order to take the fight to Kindred, will Peter be forced to consider the unthinkable?"--Provided by publisher.